2001
DOI: 10.1016/s0014-5793(00)02389-9
|View full text |Cite
|
Sign up to set email alerts
|

Human fibulin‐4: analysis of its biosynthetic processing and mRNA expression in normal and tumour tissues

Abstract: Here, we report the identification of a human orthologue of fibulin-4, along with analysis of its biosynthetic processing and mRNA expression levels in normal and tumour tissues. Comparative sequence analysis of fibulin-4 cDNAs revealed apparent polymorphisms in the signal sequence that could account for previously reported inefficient secretion in fibulin-4 transfectants. In vitro translation of fibulin-4 mRNA revealed the presence of full-length and truncated polypeptides, the latter apparently generated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 37 publications
5
52
1
Order By: Relevance
“…Moreover, high fibulin-4 expression was associated with low differentiation, advanced stage and positive lymph node status in the cervical carcinomas. Similar results have been reported in earlier studies on colon cancer; dysregulated expression of the fibulin-4 gene was shown to be associated with human colon tumorigenesis (33). However, contrasting results have also been reported for prostate cancer.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, high fibulin-4 expression was associated with low differentiation, advanced stage and positive lymph node status in the cervical carcinomas. Similar results have been reported in earlier studies on colon cancer; dysregulated expression of the fibulin-4 gene was shown to be associated with human colon tumorigenesis (33). However, contrasting results have also been reported for prostate cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Fibulin-4 plays a role in many clinical conditions such as cutis laxa (30), aortic aneurysms (31), osteoarthritis (32) and cancer (22,33). In their study on colon tumors, Gallagher et al found that the fibulin-4 gene was localized on chromosome 11q13 (33); translocations, amplifications and other rearrangements in this region are associated with a variety of human cancers (34,35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Fibulin-4 expression promotes the growth of normal and abnormal cells through p53-independent and -dependent mechanisms, respectively. With respect to the latter, signal sequence polymorphisms in the Fibulin-4 gene prevent its secretion from human colon cancer cells (28). This intracellular variant of Fibulin-4 then interacts with and inhibits the activity of p53, leading to enhanced proliferation of tumor cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas fibulin-1 was shown to mediate chemoresistance in breast cancer and furthermore seems to play a role in tumor immunosurveillance (7,8), loss of fibulin-2 results in breast cancer progression (9). Other reports imply a role of the fibulins in colon cancer tumorigenesis and breast cancer epithelialmesenchymal transition (10,11).…”
Section: Introductionmentioning
confidence: 99%